2018
DOI: 10.1002/esp.4470
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology and hillslope processes explain spatial variation in tree‐ring responses to the 1983 earthquake at Borah Peak, Idaho, USA

Abstract: Dendrogeomorphic approaches have been used to identify tree‐ring responses to earthquakes, and have the potential to contribute new paleoseismic information. However, this potential is limited by the relatively low intensity of damage from earthquakes. In this paper, we present a comparison of tree‐ring responses in multiple species to the Mw 6.9 1983 Borah Peak, Idaho earthquake across three adjacent but distinct sites with different hydrologic settings, and different types and intensities of co‐seismic mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
(113 reference statements)
2
9
0
Order By: Relevance
“…The contrasting responses on valley floors and ridges are more consistent with observations by Bekker et al. (2018), who found that tree rings were broader in a riparian zone compared to higher areas, likely driven by a rise in groundwater after the M6.9 1983 Borah Peak earthquake, Idaho. The peak ground velocity of >50−25 cm/s was similar for both the Borah and Maule earthquakes (Mohr et al., 2018; U.S. Geological Survey, 2021), both exceeding a threshold above which streamflow responses, and thus, potentially tree‐growth responses, may be expected (Mohr et al., 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The contrasting responses on valley floors and ridges are more consistent with observations by Bekker et al. (2018), who found that tree rings were broader in a riparian zone compared to higher areas, likely driven by a rise in groundwater after the M6.9 1983 Borah Peak earthquake, Idaho. The peak ground velocity of >50−25 cm/s was similar for both the Borah and Maule earthquakes (Mohr et al., 2018; U.S. Geological Survey, 2021), both exceeding a threshold above which streamflow responses, and thus, potentially tree‐growth responses, may be expected (Mohr et al., 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Tree growth can also be enhanced if neighboring and competing trees died due to earthquakes (Veblen et al., 1992), with larger individuals having the greatest survival potential (Allen et al., 2020). Earthquakes may elevate groundwater levels by increasing soil permeability and thus giving tree roots more access to water (Bekker et al., 2018; Mohr et al., 2015). Earthquakes as small as magnitude 4.6 have measurably affected tree growth (Sheppard & White, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Variability around any distance decay in landslide damage will occur because of other landscape‐level characteristics (e.g. Bekker, Metcalf, & Harley, ; Keefer, ; Marc, Hovius, Meunier, Uchida, & Hayashi, ). For example, the number of earthquake‐induced landslides varies with slope and landform (Keefer, ; Kitzberger, Veblen, & Villalba, ; Rosser & Carey, ).…”
Section: Introductionmentioning
confidence: 99%
“…fractured roots through soil movement) injury to many trees in montane forests (Allen et al, ; Jacoby, Bunker, & Bensen, ). Injury is the usual reason given for suppressed tree growth after earthquakes (Bekker et al, ; Jacoby et al, ; Wells, Duncan, & Stewart, ). Sometimes, however, trees may exhibit a growth increase after earthquakes because the death of adjacent trees leads to a reduction in neighbourhood competition and increased resources (Kitzberger et al, ; Veblen, Kitzberger, & Lara, ; Wells et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of very small rockfalls (10 1 –10 2 m 3 ) as paleoseismic indicators is a relatively recent development which is beginning to expand in scope and complexity 24,25 . Approaches may suffer from the inherent uncertainty in inferring a seismic origin because elimination of aseismic triggering of rockfall can prove difficult 26,27 .…”
Section: Introductionmentioning
confidence: 99%